THE CLINICAL PROFILES OF AVIAN INFLUENzA IN ENDEMIC AND NON-ENDEMIC REGIONS IN INDONESIA. HOSPITAL-BASED STUDIES AND ITS IMPLICATION ON CLINICAL MANAGEMENT IN THE FUTURE - Wibisono, Muhammad Jusuf; Meliana, Resti Yudhawati (Indonesian Journal of Tropical and Infectious Disease, 2010)
Indonesia is a greatest burden country of H5N1 avian influenza (AI) virus infection in the world, since first outbreak in Central Java 2005 until August 2010 there was 168 confirmed cases and 138 dead cases. The incidence increasing rapidly in widespread area endemic in Java, Sumatera, Bali and Sulawesi, and sporadic outbreaks in other areas. The World Health Organization stated that AI still became a treat in the next pandemic. H5N1 AI virus infection spreads in almost all provinces, but its endemic in Jakarta, Tangerang and Banten and in other area such Surabaya, Bali were sporadic outbreaks. There are 27 confirmed H5N1 AI infection cases in Jakarta from 296 suspected cases, while in Surabaya only 5 confirmed H5N1 AI infection cases from 12 suspected cases. The age of patient mean with H5N1 AI infection was 16.9 ± 11.6 yo in Jakarta and 24 ± 8.51 yo in Surabaya. There was no difference between male and female. Mortality rate was 77.7% in Jakarta and 60% in Surabaya. A large number of case has indirect contact history, predominantly by visiting market or areas where outbreaks of poultry disease. The clinical feature H5N1 AI virus infection could manifest as mild until severe pneumonia that often progress rapidly to ARDS. In Jakarta, 74% case showed abnormality chest radiography as bilateral pneumonia, while in Surabaya showed lobar pneumonia and bilateral pneumonia. Management patient of H5N1 AI infection is supportive therapy and antiviral, whereas a large number of cases needed mechanical ventilator support.